Blunt impacts to the back: Biomechanical response for model development. Issue 12 (18th September 2015) - Forman, Jason; Perry, Brandon; Henderson, Kyvory; Gjolaj, Joseph P.; Heltzel, Sara; Lessley, David; Riley, Patrick; Salzar, Robert; Walilko, Tim
Abstract: The development of advanced injury prediction models requires biomechanical and injury tolerance information for all regions of the body. While numerous studies have investigated injury mechanics of the thorax under frontal impact, there remains a dearth of information on the injury mechanics of the torso under blunt impact to the back. A series of hub-impact tests were performed to the back surface of the mid-thorax of four mid-size male cadavers. Repeated tests were performed to characterize the biomechanical and injury response of the thorax under various impact speeds (1.5 m/s, 3 m/s and 5.5 m/s). Deformation of the chest was recorded with a 59-gage chestband. Subject kinematics were also recorded with a high-speed optoelectronic 3D motion capture system. In the highest-severity tests, peak impact forces ranged from 6.9 to 10.5 kN. The peak change in extension angle measured between the 1st thoracic vertebra and the lumbar spine ranged from 39 to 62°. The most commonly observed injuries were strains of the costovertebral/costotransverse joint complexes, rib fractures, and strains of the interspinous and supraspinous ligaments. The majority of the rib fractures occurred in the rib neck between the costovertebral and costotransverse joints. The prevalence of rib-neck fractures suggests a novel, indirect loading mechanism resulting from bending moments generated in the rib necks caused by motion of the spine. In addition to the injury information, the biomechanical responses quantified here will facilitate the future development and validation of human body models for predicting injury risk during impact to the back.